2006
DOI: 10.2298/abs0603165m
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CYP1A in the hepatopancreas of Merluccius merluccius, Trigla lucerna, and Liza ramada (pisces) in the wider vicinity of Bar harbor Montenegro

Abstract: The expression of CYP1A, a biomarker for the presence of xenobiotic compounds, was examined in three fish species from the wider vicinity of Bar harbor in winter and spring. Induction of CYP1A was observed in winter and increased further in spring. Several PCBs were found in seawater in winter. They decreased below the limit of detection in spring, when the PAH fluorene was detected. It is concluded that the constant presence of CYP1A expression is probably due to pollutants in the environment, whereas increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The classes of cytochrome P450 isozymes, which are responsible for the biotransformation of xenobiotics, are represented in fish by the CYP1A subfamily of proteins (Stegeman and Hahn, 1994). CYP1A is a well-established biomarker of the exposure of fish to xenobiotics (Mihailović et al, 2006a(Mihailović et al, , 2006b(Mihailović et al, , 2010a(Mihailović et al, , 2010b. Furthermore, the lower percentage of oxygen measured in the water samples from SM and Bgd could indicate increased levels of organic contaminants and xenobiotics as compared to the upstream Zgd locality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classes of cytochrome P450 isozymes, which are responsible for the biotransformation of xenobiotics, are represented in fish by the CYP1A subfamily of proteins (Stegeman and Hahn, 1994). CYP1A is a well-established biomarker of the exposure of fish to xenobiotics (Mihailović et al, 2006a(Mihailović et al, , 2006b(Mihailović et al, , 2010a(Mihailović et al, , 2010b. Furthermore, the lower percentage of oxygen measured in the water samples from SM and Bgd could indicate increased levels of organic contaminants and xenobiotics as compared to the upstream Zgd locality.…”
Section: Discussionmentioning
confidence: 99%
“…), antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), glutathione transferases (GST) (which respond to exposure to reactive oxygen species (ROS), free radicals, and pollutants causing oxidative stress), lipid peroxides (oxidants, metals, etc.) (Stegeman and Hahn, 1994;Van der Oost et al, 2003;Pavlović et al, 2004;Mihailović et al, 2006aMihailović et al, , 2006bMihailović et al, , 2010aMihailović et al, , 2010bHellou et al, 2012). On the other hand, the heat shock proteins (HSPs) are an abundant and inducible class of proteins involved in stress physiology, endocrine processes, the immune response, environmental physiology, stress tolerance and acclimation (Basu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…paradoxus are limited, reports by Goksoyr and Forlin [ 43 ] have stated that fish CYP1A proteins have molecular weights ranging between 45 and 60 kDa (species dependent). Investigations by Mihailovic et al [ 34 ] on the hake, Merluccius merluccius, reported that the molecular weight of CYP1A was 55 kDa. Most studies present the CYP1A protein as a monomer [ 25 , 44 ]; therefore it was assumed that the lower molecular proteins observed in Figure 1 were degradation products formed during the isolation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…These fish species are opportunistic predators and display a feeding pattern that is spatially and seasonally variable [ 32 ]. Cape hake were selected as model species for this study because these species are of high commercial interest around the world [ 33 ] and studies concerning the development and optimization of biomarker assays on Merluccius species are extremely limited [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 In order to assess the exposure to or the effects of environmental pollutants on aquatic ecosystems, different biomarkers are examined, i.e. [2][3][4] The induction of CYP1A occurs through ligand binding of PAHs and PCBs to a cytoplasmic receptor, known as the hydrocarbon receptor. 1 The phase I biotransformation enzymes, notably CYP1A, belong to a group of very sensitive biomarkers in fish.…”
Section: Introductionmentioning
confidence: 99%